(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Cluster of pneumonia infection emerged in Wuhan, China due to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Additionally, more than 190 countries have confirmed 82 million cases of SARS-CoV-2 infection. Currently, there is a SARS-CoV-2 epidemic, and no effective prophylactic methods are available. A vaccine is considered as an effective method to restrict an epidemic. Several vaccine designing techniques have been established, which is enabling researchers from various institutes for developing vaccine towards SARS-CoV-2 infections. In this review, we condense the development of vaccine research against SARS-CoV-2.